Real time monitoring bivalve behavior ... - Witbaard, Rob; Fischer, Philipp (SEANOE, 2019)
ReMoBiB (remote monitoring of bivalve behavior). The project aimed at deploying a so called valve gape monitor and connect it to a underwater node to generate an continuous online accesible data stream of valve gape measurement. The project aimed to demonstrate the possibility to use shell valve gape as a bio-monitor in addition to monitoring of more traditional environmental monitoring techniques. At the same time we wanted to test the possibility to connect this equipment to the COSYNA underwater node at Helgoland. For this, the existing stand alone equipment developed by NIOZ had to be adapted to enable connection and data tranfer. The scientific aim of the project was to establish the relationship between shell gape (filtration activity) of Arctica islandica and environmental factors (Salinity, Temperature, Chlorophyll, light) at the southern limit of its distribution. This is done by collecting a continuous observational time series on shell gaping behaviour covering at least an entire year, while at ...